2013
DOI: 10.1016/j.drugalcdep.2013.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Association of cannabis use with opioid outcomes among opioid-dependent youth

Abstract: Objective Cannabis use is common among opioid-dependent patients, but studies of its association with treatment outcome are mixed. In this secondary analysis, the association of cannabis use with opioid treatment outcome is assessed. Methods In the main study, participants (N=152) aged 15-21 years were randomized to receive psychosocial treatments and either a 12-week course of buprenorphine-naloxone with a dose taper to zero in weeks 9-12, or a 2-week detoxification with buprenorphine-naloxone. Drug use was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…On the other hand, continuing to use an addictive drug, such as marijuana, could interfere with efforts to achieve abstinence from other drugs. Or it may have no effect (Budney et al, 1998; Hill et al, 2013; Church et al, 2001; Epstein and Preston, 2003; Nirenberg et al, 1996; Saxon et al, 1993; Alessi et al, 2011; Budney et al, 1996; Darke et al, 2006). Prior studies lend some support for each of these possibilities and hence findings among previously published studies are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, continuing to use an addictive drug, such as marijuana, could interfere with efforts to achieve abstinence from other drugs. Or it may have no effect (Budney et al, 1998; Hill et al, 2013; Church et al, 2001; Epstein and Preston, 2003; Nirenberg et al, 1996; Saxon et al, 1993; Alessi et al, 2011; Budney et al, 1996; Darke et al, 2006). Prior studies lend some support for each of these possibilities and hence findings among previously published studies are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…But findings about marijuana’s effects on use of other substances and the need to address it during addiction treatment for other substances are not uniform (Hill et al, 2013; Wasserman et al, 1998; Church et al, 2001; Epstein and Preston, 2003; Nirenberg et al, 1996; Saxon et al, 1993; Aharonovich et al, 2005; Alessi et al, 2011; Budney et al, 1996; Kadden et al, 2009). Many find no association between marijuana use and outcome of addiction treatment for other substances (Budney et al, 1996; Church et al, 2001; Epstein and Preston, 2003; Hill et al, 2013; Nirenberg et al, 1996; Saxon et al, 1993) and one small study suggested that marijuana use helped crack cocaine addiction (Labigalini et al, 1999). Another small study, however, suggests that addressing marijuana use may lead to more use of alcohol (Peters and Hughes, 2010) and at least two prospective studies suggest that marijuana use is associated with worse addiction treatment outcomes (Aharonovich et al, 2005; Wasserman et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are differences in the biological and social mechanisms involved with youth and adults, so cannabis may differentially influence treatment outcomes in the two populations. Because a consistent age range is not used to define youth in MMT studies [ 28 , 39 , 40 ], MMT studies will be included in the subgroup analysis if the authors specify that they are investigating youths or adolescents.…”
Section: Methods and Designmentioning
confidence: 99%
“…For example, Wasserman et al [ 24 ] found that cannabis use at baseline and throughout the study period was significantly associated with subsequent heroin use during treatment, whereas Scavone et al [ 14 ] found that patients using cannabis during the study reported significantly less daily expenditure on acquiring opioids. Most studies, however, have failed to produce a statistically significant association between cannabis use and MMT retention or illicit opioid use [ 13 , 25 28 ]. Epstein and Preston [ 26 ] found that cannabis use increased other outcomes such as jail time and family conflict, suggesting that its use during MMT may act indirectly via social and lifestyle risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this limited and conflicting evidence, many OAT programmes require abstinence from cannabis and other drugs as a sign of stability (e.g. to be eligible for take‐home dosing privileges) . Given the urgent need to identify novel effective strategies to address the ongoing opioid crisis in North America, and in the context of the increasing availability of cannabis (through both medical and adult‐use laws), it is critical to understand more clearly the impacts of cannabis use on OAT outcomes—including its potential therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%